PERSEPSI MASYARAKAT TERHADAP PELACUR JALANAN DI RT 004 KELURAHAN BUKIT BATREM KECAMATAN DUMAI TIMUR KOTA DUMAI - Arvanto Panggabean; Nurhamlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to determine the public perception to street prostitutes. This research was conducted in RT 004 Bukit Batrem Village, East Dumai Subdistrict, Dumai City with the number of respondents 61 families (heads of families) from the total community of RT 004 as many as 159 families (heads of families). The research data were obtained through research instruments regarding the characteristics of the respondent's identity, the public's perception to street prostitutes, and factors that influence the public's perception. This study uses a survey method with a quantitative approach. Data analysis in this study also describes the data by presenting the mean, median, maximum value, minimum value and distribution table. In this study the authors used the application of SPSS (Statistic Program for Social Sciences) version 20.0. This research is generally used to explain the characteristics of the RT 004 community as respondents and also their response to the presence of street prostitutes in their residential areas. Where in the characteristics of the respondents, the writer looks at the gender, age, ethnicity, level of education, occupation, and length of stay of each respondent. As for the community response, the author has provided several lists of questions in the research questionnaire that has been made in advance. For the perception itself the writer divides it into two categories, namely within the optimal limit if the community can survive (Homeostatis) and outside the optimal limit if the community is disturbed by the presence of street prostitutes and feels stressed.  Keywords : Perception, Street prostitutes